Vacuum therapy prevents corporeal veno-occlusive dysfunction and penile shrinkage in a cavernosal nerve injured rat model - Sheng-Qiang Qian; Feng Qin; Shuang Zhang; Yang Yang; Qiang Wei; Run Wang; Jiu-Hong Yuan (Asian Journal of Andrology, 2020)
Erectile dysfunction and penile shrinkage are the common complications after radical prostatectomy. Penile rehabilitation is widely applied after the surgery. Vacuum therapy is one of the three penile rehabilitation methods used in the clinical setting, but its mechanism is not well known. This study was designed to investigate whether vacuum erectile device (VED) can prevent corporeal veno-occlusive dysfunction and penile shrinkage in the bilateral cavernous nerve crush (BCNC) rat model. Adult male Sprague–Dawley rats were randomly assigned into three groups: sham group, BCNC group, and BCNC + VED group. After 4 weeks, penile length and intracavernosal pressure (ICP) were measured, and then the middle part of the penis was harvested after dynamic infusion cavernosometry to complete the following items: smooth muscle/collagen ratios and collagen I/III ratios; ultramicrostructure of the tunica albuginea, endothelial cell, and smooth muscle cell; and the expression of calponin-1 and osteopontin. The penile shortening, peak ICP and ICP drop rate after alprostadil injection were significantly improved with vacuum therapy after 4-week treatment. Compared with BCNC group, VED significantly increased smooth muscle/collagen ratios, decreased collagen I/III ratios, and preserved the ultramicrostructure of the tunica albuginea, endothelial cell, and smooth muscle cell. The data also showed that animals exposed to VED could partially reverse the expression of calponin-1 and osteopontin induced by BCNC. In conclusion, vacuum therapy is effective to prevent penile shrinkage and veno-occlusive dysfunction in penile rehabilitation, which may be associated with well-preserved structure and function of the tunica albuginea, endothelial cell, and smooth muscle cell.